(untitled) (Research, Society and Development, 2021)
This work aims to investigate how the teaching of Geodiversity is present in dissertations and theses of graduate programs in Brazil (2009-2019). A quali-quantitative research of bibliographic nature was carried out, whose data were collected in the month of November 2020, at the Biblioteca Digital Brasileira de Teses e Dissertações, through specific research configurations.17 papers were found, of which 16 are dissertations and only one is a thesis presented in graduate programs, defended between 2009 and 2019, in 15 higher education institutions, namely: UFSC, USP, PUC-Rio, UFRGS, UEPG, UNESP, UFSCar, UFV, UEL, UFSM, UFC, UFRN, UFPE, UFTM e UNIOESTE. Of all the works, only one really addresses the theme of geovidersity in the school environment. Thus, it can be concluded that the theme of Geodiversity is present in some works, but in a timid and incipient way, especially when it comes to the teaching of Geodiversity.